MΦ macrophage – N0 neutrophil dialogue in the presence of TNF-α affects the endothelium - VATAMANU, Sergiu-Marian; ȚUCUREANU, Monica; MIHĂILĂ, Andreea; BUTOI, Elena; FARKAS, Anca (Studia Universitatis Babeș-Bolyai Biologia, 2025)
Tumor necrosis factor-alpha (TNF-α) plays a pivotal role in the bi-directional dialogue between macrophages and neutrophils during the pre- and post- lesional stages of atherogenesis. This pro-inflammatory cytokine orchestrates a complex interplay between these immune cells, leading to the activation and recruitment of additional leukocytes, and the modulation of endothelial cell function, which collectively drive plaque formation and progression. Elevated levels of TNF-α result in the upregulation of adhesion molecules on the surface of endothelial cells. The cross-talk between macrophages and neutrophils, mediated by TNF-α, also leads to the release of soluble factors that have profound effects on the endothelium. Notably, these factors induce endothelial cell apoptosis via mechanisms involving caspase-3 activation, further contributing to the dysfunction and eventual denudation of the endothelial layer, a hallmark of atherogenesis. At molecular level, TNF-α exposure significantly upregulates the expression of pro-inflammatory mediators in macrophages, including interleukin-1 beta (IL-1β), inducible nitric oxide synthase (iNOS), and the activation of key signaling pathways such as the activation of mitogen-activated protein kinase (MAPK) signaling pathway and stress-activated protein kinase/c-Jun N-terminal kinase (SAPK/JNK). This bi-directional dialogue not only sustains chronic inflammation, but also amplifies the pathogenic processes underlying atherosclerosis, suggesting that targeting TNF-α and its downstream effects could represent a therapeutic strategy to mitigate disease progression. In this study, we aimed at investigating the dialogue between macrophages and unpolarized neutrophils, by assessing the biomarkers leading to cells activation and their differentiation towards a pro-inflammatory phenotype. The effects of TNF-α were explored in the context of inflammation in the arterial wall, for a better understating of atherogenesis. The study results indicated a low intensity inflammatory response, characterized by the up-regulation of key molecules involved in cell signaling for differentiation towards an inflammatory phenotype but not in the production of significant amounts of cytokines and enzymes. Article history: Received 31 March 2025; Revised 28 May 2025; Accepted 29 May 2025; Available online 25 June 2025